Olbert’s Balloon Dilatation as a Minimally Invasive Possibility of Treating Ureteral Stricture After Complicated URS-L in Children - Halinski, Adam; Halinski, Andrzej; Halinski, Paweł (Frontiers in Pediatrics, 2022)
Olbert’s balloon dilatation is a surgical technique used for the treatment of ureteral stricture. Although it is more frequently used in adults, due to the advancing miniaturization of the equipment, this technique has become possible in children. We would like to present 5 cases of Olbert’s balloon dilatation carried out in children with ureteral stricture after complicated URS-L, aged 12 to 17 years. All of these children were diagnosed for at least 6 months. Duration of the stone in the ureter varied from 6 to 18 months. The symptoms were abdominal pain, renal colic pain, UTI, fever, vomiting and nausea. Ultrasound (US) revealed hydronephrosis and ureter dilatation above the stone. All of these children had grade-3 hydronephrosis based on Onen grading system during admission to the hospital. The lack of renal function on DMSA scan was observed with an average of 20%. JJ-stent was inserted as a first treatement. Retrograde pyelogram revealed ureteral stricture at a lengt of 1-1,7 cm in the place where stone was ingrown. Olbert’s Balloon dilatation under fluoroscopy was performed successfully in all children. We achieved an efficacy of 66%. Renal function increased to the average of 36% on DMSA 3 months after surgery. The level of creatinine shaped at average 0.6. On US, two children had no hydronephrosis while one child had grade-1 hydronephrosis. The longest follow up is now 4 years, with the same good results. In conclusion, Olbert’s balloon dilatation is an effective, safe and minimally invasive tool for ureteral stricture in the hands of endourological experienced paediatric urologist. But more prospective, randomized trials are still needed.